Aspects of the biology, population ecology and behaviour of the sable antelope, Hippotragus niger niger, (Harris, 1838) in the Rhodes Matopos National Park, Rhodesia - Botha, J du Plessis (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 1973.